OBSTETRIC OUTCOMES OF INTRAUTERINE GROWTH RESTRICTION CASES FROM 37 WEEKS AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate maternal outcomes in cases of fetal growth restriction from 37 weeks of gestation at Hanoi Obstetrics and Gynecology Hospital.Objects and Methods: This prospective cross-sectional study included 139 pregnant women diagnosed with fetal growth restriction from 37 weeks of gestation, who were followed up and delivered at Hanoi Obstetrics and Gynecology Hospital between January 2025 and October 2025.Results: The mean gestational age at pregnancy termination was 38.1 ± 0.7 weeks. The cesarean section rate was 77%, while vaginal delivery accounted for 23%. The most common indications for cesarean delivery were previous cesarean section (19.4%) and fetal distress (9.4%). Labor induction was performed in 5.8% of cases, with a success rate of 75% and a failure rate of 25%. The mean length of maternal hospital stay was 3.33 days. The proportion of hospital stays longer than 3 days was 45.8% among women who underwent cesarean delivery and 18.8% among those who had vaginal delivery.Conclusion: The timing of pregnancy termination should be carefully determined by balancing the benefits of continued surveillance against the risk of intrauterine fetal demise, and is generally recommended after 38 weeks of gestation. Fetal growth restriction alone is not an absolute indication for cesarean delivery. In cases of cesarean birth, the length of hospital stay is longer compared with vaginal delivery.
Keywords: Fetal growth restriction; pregnancy outcomes.